2002
DOI: 10.1007/s10006-002-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

Fehlbildungen der Kieferhöhle bei Neurofibromatose Typ 1

Abstract: Malformations of the face are frequently presented as case reports in the literature. Emphasis is given to the elephantiasis-like tumor growth of the face in certain patients with NF1. The underlying pathology has not yet been fully understood. This report provides evidence that in the midfacial region the overgrowth is predominantly caused by the plexiform neurofibroma itself and that the bones can even be hypoplastic and show scoliosis-like malformation compared to the nonaffected side. These findings are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Altered paranasal sinuses in NF1. Systematic studies on the radiological morphology of paranasal sinuses in the context of NF1 were performed for the maxillary sinus (40). The in vivo 35: 349-361 (2021) results suggest the relationship between unilateral hypoplastic maxillary sinus and orbital deformation of the same side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered paranasal sinuses in NF1. Systematic studies on the radiological morphology of paranasal sinuses in the context of NF1 were performed for the maxillary sinus (40). The in vivo 35: 349-361 (2021) results suggest the relationship between unilateral hypoplastic maxillary sinus and orbital deformation of the same side.…”
Section: Discussionmentioning
confidence: 99%
“…These radiological signs indicate that the tumour may have grown beyond the orbit into the face. In general, the cheek is also largely infiltrated by the tumour, which typically grows in continuity with the orbital mass (39,40,67). From this established constellation of morphological findings, one can deduce that the hypoplastic maxillary sinus in NF1 is usually not an independent or 'spontaneous' event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Usually, this manifestation occurs unilaterally and is often associated with plexiform neurofibromas in the distribution of the trigeminal nerve. 2 However, Riccardi reported that sphenoid wing dysplasia can occur either with or without a peripheral neurofibroma (pNF). 3 Jackson et al 4 classified orbitotemporal neurofibromatosis into three groups (group 1, orbital soft-tissue involvement only with a seeing eye; group 2, orbital soft-tissue and significant bone involvement with a seeing eye; and group 3, orbital soft-tissue and significant bone involvement with a blind or absent eye).…”
mentioning
confidence: 99%
“…1 Usually, this manifestation occurs unilaterally and is often associated with plexiform neurofibromas in the distribution of the trigeminal nerve. 2 However, Riccardi reported that sphenoid wing dysplasia can occur either with or without a peripheral neurofibroma (pNF). 3 Jackson et al 4 classified orbitotemporal neurofibromatosis into three groups (group 1, orbital soft-tissue involvement only with a seeing eye; group 2, orbital soft-tissue and significant bone involvement with a seeing eye; and group 3, orbital soft-tissue and significant bone involvement with a blind or absent eye).…”
mentioning
confidence: 99%